Choice of currency in bond issuance and the international role of currencies - Nikolaus Siegfried; Emilia Simeonova; Cristina Vespro (European Central Bank (ECB), 2007)
This paper investigates bond issuance of non-financial corporations in advanced economies during the period 1999-2003, attempting to understand motives for issuing in foreign currency, and determinants for the choice of currency. We consider the following influences on the currency choice when issuing foreign currency denominated debt: the microeconomic characteristics of the firm, the macroeconomic institutional environment and the financial particularities of the bond issue. We find that in addition to cost minimisation, hedging motives and the desire to establish an investor base influences the choice of currency. At the same time, market conventions and regulation also affect the choice.
Keywords: C25; E44; F23; G32; 330; Bond issuance; conditional logit; Foreign currency denominated debt; nested logit; Panel logit; Internationale Anleihe; Währung; Eurobond; Euro; Währungswettbewerb; EU-Staaten; Welt